THE IMPORTANCE OF MICROORGANISMS IN INCREASING SOIL FERTILITY AND THEIR STUDY - Anorboev , Akbar (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
This article highlights the types of soil microorganisms, their ecological significance, and their impact on soil fertility. During the study, the activities of bacteria, fungi, actinomycetes, and other microorganisms were analyzed, emphasizing their role in plant growth and in the decomposition of organic matter. In addition, the article provides information on the effects of anthropogenic factors—such as chemical fertilizers, pesticides, and climate change—on soil microflora. The results obtained contribute to strengthening the scientific basis for the application of biological methods in soil ecology and agriculture.